IBM SANnav management portal v2.2.X implementation guide storage - Gucer, Vasfi; Jehnen, Kai; Kurkowski, Piotr; Lonzer, Hartmut; Preinl, Dirk; Scheld, Thomas; Tsonev, Simeon (IBM Redbooks, 2023)
IBM® SANnav Management Portal and IBM SANnav Global View empower IT administrators to be more efficient and productive by providing comprehensive visibility into the SAN environment. These tools transform information about SAN behavior and performance into actionable insights, allowing administrators to quickly identify, isolate, and correct problems before they impact the business. In addition, SANnav Management Portal and SANnav Global View accelerate administrative tasks by simplifying workflows and automating redundant steps, making it easier for organizations to realize their goal of an autonomous SAN. This IBM Redbooks® publication introduces IBM SANnav Management Portal and SANnav Global View, and covers the installation, customization, operation, and troubleshooting of the IBM SANnav Management Portal. This book is targeted at IT and network administrators.
Keywords: IBM Global Services; Storage area networks (Computer networks); Computer storage devices; Réseaux de stockage (Informatique); Ordinateurs; Mémoires